MEMORY, POSTMEMORY, AND PLACE IN THE SYNAGOGUES OF ROMAN SYRIA. - STERN, KAREN B. (Bulletin of the Institute of Classical Studies, 2019)
Considerations of Jews in antiquity commonly emphasize the role of common institutions (such as the Jerusalem Temple) and shared traumatic experiences (such as exile) in generating distinctive modes of memory formation and memorialization. This paper takes a different approach. By drawing from recent discussions of memory and postmemory developed in the fields of sociology, anthropology, and visual studies, and by considering diverse data from wall paintings, ceiling decorations, inscriptions, graffiti, and mosaics, the ensuing analysis demonstrates how variegated were the practices and dynamics of memory among Jews living in Roman Syria and elsewhere. Asking different types of questions about memorial practices documented in synagogues and surrounding buildings in Dura‐Europos and Apamea challenges regnant assumptions about commonalities in Jewish memory and argues for a more localized and spatial approach to Jewish memory practices, the dynamics of which were as personal as they were collective, and as particular as they were locally contingent.